Choline intake and associations with egg and dairy consumption among pregnant women attending a high-risk antenatal clinic in South Africa: the NuEMI study - Liska Robb; Gina Joubert; Elizabeth Margaretha Jordaan; Jennifer Ngounda; Corinna May Walsh (BMC, 2021)
Abstract Background The importance of adequate choline intake during pregnancy has been well documented, but low intake is common. Total choline intake, main food sources of choline, as well as associations between choline intake and egg and dairy consumption were determined in a sample of pregnant women attending the high-risk antenatal clinic at a regional hospital in Bloemfontein, South Africa. Methods A cross-sectional study design was used. Trained fieldworkers collected dietary intake data using a validated quantified food frequency questionnaire (QFFQ), after which all food items were matched to foods in the USDA Database for the Choline Content of Common Foods (Release 2) to quantify choline intake. Logistic regression with backward selection (p < 0.05) was used to determine whether egg and dairy consumption were independently associated with a choline intake below the adequate intake (AI) level. Results The median daily intake of choline was 275 mg (interquartile range 185 mg - 387 mg) (N = 681). Most participants (84.7%) consumed less than the AI of 450 mg/day for choline. Meat and meat products, cereals, eggs and dairy contributed mostly to choline intake. Food items that contributed most to choline intake included full-cream milk, maize porridge, brown bread, deep-fried potatoes and deep-fried dough (vetkoek). A choline intake below the AI was significantly associated with lower egg and dairy intakes (p < 0.0001 and p = 0.0002 respectively). Conclusion Most pregnant women in the current study had choline intakes below the AI. It is recommended that public health messaging targeted at pregnant women promote the consumption of foods that can significantly contribute to choline intake, such as eggs and dairy.